The Effect Of Tax Planning, Profitability, Liquidity, And Company Size On Earnings Management With Tax Rate Reduction As A Moderator (In Building Construction Companies Listed On The Indonesia Stock Exchange For The 2019–2023 Period) - Rahman, Muhammad Ziddan Rahman; Kismanah, Imas (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the influence of tax planning, profitability, liquidity, and company size on earnings management, with tax rate reduction as a moderating variable. The research focuses on construction companies listed on the Indonesia Stock Exchange from 2019 to 2023. The findings indicate that while tax planning does not significantly affect earnings management, profitability and liquidity play crucial roles in influencing profit management practices. Additionally, tax rate reductions enhance the effects of profitability and liquidity on earnings management. The results emphasize the need for improved corporate governance to prevent profit manipulation and ensure compliance with fiscal regulations.